Family social support and the self-esteem of breast cancer patients undergoing neoadjuvant chemotherapy - Erik Aprilianto; Sih Ageng Lumadi; Feriana Ira Handian (SAGE Publishing, 2021)
Background: Neoadjuvant chemotherapy is the first step in breast cancer treatment. However, the medical procedure causes stressors on the self-concept of patients, especially low self-esteem, due to the decrease in the function of their limbs. This research aims to investigate the correlation between family social support and the self-esteem of breast cancer patients undergoing neoadjuvant chemotherapy. It was conducted using a cross-sectional approach. Design and Methods: A sample of 56 people was selected by a simple random sampling technique, using a family social support questionnaire and the Rosenberg Self Esteem Scale. Results: Based on the Spearman Rho statistical test, it was found that the value of p was 0.000 with a correlation coefficient value of 0.762. This indicated that there was a strong positive correlation between family social support and patient self-esteem. Conclusions: Families are the closest systems to patients that play an important role as a coping strategy and in disease management. Therefore, it is suggested that family community groups should be developed among families that have breast cancer patients through social networking.